Graphene Hybrids: Nitrogen‐Doped Graphene/Carbon Nanotube Hybrids: In Situ Formation on Bifunctional Catalysts and Their Superior Electrocatalytic Activity for Oxygen Evolution/Reduction Reaction (Small 11/2014). Issue 11 (June 2014) - Tian, Gui‐Li; Zhao, Meng‐Qiang; Yu, Dingshan; Kong, Xiang‐Yi; Huang, Jia‐Qi; Zhang, Qiang; Wei, Fei
<x xml:space="preserve">Abstract</x> The development of highly‐active bifunctional catalysts at low cost for both oxygen reduction and oxygen evolution reactions are greatly required for fuel cells, metal–air batteries, and water splitting. As reported by Q. Zhang, F. Wei, and co‐workers on page 2251, nitrogen‐doped graphene/single‐walled carbon nanotube hybrids exhibit very high activity for both the oxygen reduction reaction and oxygen evolution reaction, which opens up new avenues for energy conversion technologies based on earth‐abundant, scalable, precious‐metal‐free catalysts. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>